2022
DOI: 10.1186/s13071-021-05123-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deworming medication on anaemia among children aged 6–59 months in sub-Saharan Africa

Abstract: Background Despite the limited knowledge regarding the effects of deworming medication (DM) on nutritional indicators in sub-Saharan Africa (SSA), deworming programmes continue to be implemented in resource-limited countries. Therefore, the current study aimed to examine the effects of DM on anaemia among children aged 6–59 months in SSA. Methods The analysis was performed using data obtained from 17 demographic and health surveys (DHSs) conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…Consistent with other studies [ 36 38 ], children who were dewormed were less likely to be anaemic. Worms may compete for nutrients in the body including vitamin A and as a result induce chronic intestinal blood loss [ 36 , 37 ]. Therefore, deworming prevents any infections that cause of iron loss which prevents anemia.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with other studies [ 36 38 ], children who were dewormed were less likely to be anaemic. Worms may compete for nutrients in the body including vitamin A and as a result induce chronic intestinal blood loss [ 36 , 37 ]. Therefore, deworming prevents any infections that cause of iron loss which prevents anemia.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the current study indicated that children who had not taken intestinal parasite deworming medicine in the previous 6 months were also at a higher risk of anaemia. This finding was consistent with the Bauleni et al finding [ 74 ], which examined the effects of deworming medication on anaemia among children aged 6–59 months in 17 SSA; showed that children who did not receive deworming medication had increased odds of being anaemic [ 74 ]. This may be due to the fact that intestinal parasites can cause anaemia [ 75 ], and treating intestinal parasites with deworming medication can reduce the risk of childhood anaemia.…”
Section: Discussionsupporting
confidence: 91%
“…Further, deworming medication was found to protect against anemia, likely due to its effect on soil-transmitted helminths that cause iron and protein loss [37]. This is consistent with studies from Sub-Saharan Africa and Bangladesh [38,39], but at odds with studies from Ethiopia, Rwanda, and Namibia [13,41]. To further enhance the reduction of childhood anemia, the Rwandan government and other stakeholders should strengthen existing interventions like deworming and vitamin A supplements by increasing country-wide coverage and compliance rate among children aged 6-23 months.…”
Section: Determinants Of Anemia In Children Aged 6-23 Monthssupporting
confidence: 78%